Asset Valuation with the Aim of Asset Write-off in Kupang Regency - Geraldy Antonio Pah; Nikson Tameno; Cicilia Apriliana Tungga (Formosa Journal of Sustainable Research, 2023)
This research aims to assess assets and determine the fair value of motor vehicles at the Kupang Regency Regional Financial and Asset Management Agency. This research was conducted on Regional Assets in the form of vehicles totaling 8 assets, namely: Win MCB, Daihatsu Feroza, Toyota KF, Caterpilar 90T, Komatsu GD31RC, Fiat ALLIS D9BIT, Barata MGT6, Excavator 320C. This research is quantitative descriptive research where the data obtained from the research population sample is analyzed according to the statistical methods used and then interpreted. In this research, the researcher carried out data analysis by making an assessment work paper. The assessment work paper in this case is estimated using Microsoft Excel. Components such as vehicle price, year of vehicle purchase, physical condition, etc. are made on a Microsoft Excel worksheet by including estimated adjustments for the assessment report. This assessment process is carried out using the Cost Approach. The results of the valuation analysis using a cost approach for the Win MCB, Daihatsu Feroza, Toyota KF, Caterpilar 90T, Komatsu GD31RC, Fiat ALLIS D9BIT, Barata MGT6, Excavator 320C assets obtained a market value of IDR 57,520,000 and a Liquidation Value of IDR 46,516,000 and it is hoped that the results of this research can be used as a reference for motor vehicle asset assessment techniques in the Kupang Regency Regional Government for the purpose of asset write-off